Assessment of sexual dysfunction in patients with multiple sclerosis: a perspective from neurologist - Mariana Gaviria- Carrillo; Silvia Juliana Bueno-Florez; Paola Andrea Ortiz-Salas (BMC Neurology, 2022)
Highlights • Sexual dysfunction among people with multiple sclerosis (pwMS) is frequent and has an impact on quality of life. • Neurologists are concerned about sexual function in pwMS. • Patients usually report sexual dysfunction to neurologists. • There is still a gap in the treatment and evaluation of sexual dysfunction in pwMS.